Utility of Cell Blocks from Lymph Node Aspirates to Improve the Diagnostic Accuracy of Fine Needle Aspiration Cytology: A Cross-sectional Observational Study from Eastern India - Upajna Pal; Abhinandan Bayen; Debajyoti Nanda; Manisha Sarkar; Dipanwita Nag (Journal of Clinical and Diagnostic Research)
Introduction: Fine Needle Aspiration Cytology (FNAC) has been the primary modality for diagnosing lymph node enlargement, although it comes with its own share of fallacies and pitfalls. Cell blocks can be prepared from material obtained in the same sitting as FNAC, providing morphological details and preserving architectural patterns such as cell balls, three-dimensional clusters, excellent cytoplasmic and nuclear details, and individual cell characteristics. Aim: To determine the utility of cell blocks in improving the diagnostic accuracy of lymph node aspirates. Materials and Methods: This cross-sectional observational study was conducted with 50 patients who presented with visible or palpable lymph node enlargement over a period of one year (January 2021 to December 2021) at the Medical College and Hospital, Kolkata, West Bengal, India. Patients underwent Fine Needle Aspiration (FNA) from the lymph nodes, followed by cell block preparation in the same sitting. Material for the cell block was obtained by an additional pass with a 16-18G needle and was prepared using the plasma thrombin method, followed by formalin fixation, routine processing, Haematoxylin and Eosin (H&E) staining, and immunohistochemical staining. Patients were subsequently followed-up for tru-cut and excision biopsies. FNAC and cell block slides were examined by two expert pathologists to reach a final diagnosis. The diagnostic validity of the cell block was reported in terms of sensitivity, specificity, and accuracy. The Cohen’s kappa statistical coefficient test was performed to represent diagnostic accuracy. A p-value of less than 0.05 was considered significant. Results: Out of the total 50 cases, 21 (42%) were diagnosed as infective or reactive lymphadenopathy, 9 (18%) cases were lymphoproliferative disorders, and 20 (40%) cases were metastatic deposits based on cytology and cell block morphology. One case of reactive lymphadenopathy underwent lymph node excision biopsy and was ultimately diagnosed as Non-Hodgkin’s lymphoma. Three cases (6%) were diagnosed as classical Hodgkin’s lymphoma (positive for CD15 and CD30) based on the cell block, 6 (12%) cases were Non-Hodgkin’s lymphoma and 20 (40%) cases were metastatic deposits identified on FNA cytology and cell block. The overall sensitivity of the cell block in diagnosing lymph node aspirates was 97.87%, with a specificity of 80% and an accuracy rate of 96.15%. Cohen’s kappa calculated for FNAC and cell block was 0.724, indicating substantial agreement (95.5% agreement). Conclusion: Cell blocks can be efficiently utilised from lymph node aspirates to improve the diagnostic accuracy of lymph node FNAC, even before an excision biopsy is performed in patients who are unfit for invasive surgical procedures. Immunohistochemistry (IHC) in cell blocks can also be effectively implemented to differentiate between lymphoma and metastatic deposits.